Using Gamification Techniques in Teaching English: Empowering Student’s Interest in ELT Classrooms - Umi Mujiarni; Indra Perdana; Karani, Elanneri (EJI (English Journal of Indragiri): Studies in Education, Literature, and Linguistics, 2025)
The application of gamification in English language learning aims to overcome the low motivation and student engagement that often occurs due to conventional teaching methods. This research uses a gamification approach through interactive educational video media designed to deliver vocabulary and grammar materials in an engaging manner. The method was applied in teaching and learning activities and observed to assess student responses and learning outcomes. The results showed an increase in students' enthusiasm, active participation, and understanding of the material taught. Students are more likely to remember vocabulary and understand grammar concepts, and show positive responses to learning that becomes more fun and less boring. The findings confirm that gamification through educational videos is effective in creating an interactive learning atmosphere and improving the quality of English learning.